Lepton masses and mixing in a scotogenic model - Fortes, E. C. F. S.; Machado, A. C. B.; Montano, J.; Pleitez, V [UNESP] (Elsevier B.V., 2020)
We consider an extension of the standard model with three Higgs doublets and S-3 x Z(2) discrete symmetries. Two of the scalar doublets are inert due to the S-3 symmetry and the Z(2) symmetry ensures that the right-handed neutrinos generate active neutrinos masses at one-loop via the scotogenic mechanism. We have also calculated all the mass spectra in the scalar and lepton sectors and accommodated the leptonic mixing matrix as well. Constraints on the parameters of the model coming from the lepton flavor violating decay mu -> e gamma are obtained, using the current and the upcoming experimental limits. We also use those constraints to predict the induced mu -> ee (e ) over bar channel at one-loop. (C) 2020 Published by Elsevier B.V.